REPRODUCTION, FECUNDITY AND SEX RATIO OF THE GREEN TIGER PRAWN, PENAEUS SEMISULCATUS DE HAAN - Thomas, M M (Indian Journal of Fisheries, 2011)
Investigations on the reproduction, gonado-somatic index, fecundity and sexratio of Penaeus semisulcatus were carried out at Mandapam Camp, from April,1967 to March, 1969. Five stages of maturity could be differentiated depending on tliecolour of the ovarian lobes, the thickness of the ovary and the size of the ova. Femaleprawns with mature ovaries occurred throughout the year showing that they spawncontinuously, the peak season being June to September and January to February.The gonado-somatic index exhibited a variation from 2.2 to 13.2. The minimumsize at maturity in females was found to be 23 mm carapace length. The fecundityof the species was found to range between 51,605 and 6,60,904. There was norelation between the fecundity and the length of prawn, weight of prawn or weightof ovary. The samples examined contained more or less same number of malesand females, although, during certain months the males were more in numberwhile in other months the females were dominating.